EVALUATION OF THE RESULTS OF PERCUTANEOUS PINNING OF SUPRACONDYLAR FRACTURES OF THE HUMERUS IN CHILDREN (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluation of the results of percutaneous pinning of supracondylar fractures of the humerus in children at Hanoi Medical University Hospital.Subjects and Methods: Retrospective study describing 46 patients diagnosed with closed supracondylar humeral fractures, treated with closed reduction and percutaneous pin placement at Hanoi Medical University Hospital from October 2021 to June 2025.Results: The study included 46 patients, the average age was 6.67±2.73 (2-12); the male/female ratio was 1.3/1. The injured side with the left/right ratio: 25/21 cases. The average time from injury to surgery was 16.83±29.37 hours, in which the majority was 15 degrees (according to Flynn).Conclusion: Closed reduction and percutaneous pinning provide good short-term results with small incisions, no blood loss and short hospital stay. This is an effective and safe option for the treatment of closed supracondylar humeral fractures in children.
Keywords: Supracondylar fractures of the humerus in children, closed reduction, percutaneous pinning.